EARTHEN-BUILDING CULTURES AND SEISMIC HAZARD: CHILEAN TRADITIONAL ARCHITECTURE - Jorquera, Natalia (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
This article will disclose the partial results of a doctoral thesis developed between 2009-2012 within the Department of Technology of the Faculty of Architecture of the University of Florence. The inal results, were presented during TERRA 2012 conference. The core aim of the thesis is the seismic-risk assessment of different building cultures in Chilean territory that use earth as the predominant building material, in order to propose retroitting techniques to reduce the threat. The research is inserted within the context of recent major earthquakes that have affected Chile, which have been particularly destructive to earthen buildings, raising the need to develop preventive actions to preserve this relevant heritage.